Facilitating osteogenesis of Hydroxyapatite granules by Autogenous bone marrow (Mustansiria Dental Journal, 2018)
The aim study to evaluate whether Hydroxyapatite granules alone or in combinationwith autogenous bone marrow can facilitate bone formation. Materials and Methods: (8)dogs of both sexes were used as a model in this experimental study ,they were divided intotwo groups , the control group in which ( 4) dogs were operated on in this group receivedHydroxyapatite granules alone in defect created in the body of mandible (1cm) in diameterand experimental group in which (4)dogs were operated on in this group receivedHydroxyapatite granules mixed with autogenous bone marrow implanted in the defect alsocreated in the body of mandible (1cm) in diameter .Alkaline phosphatase enzyme (ALP)used as parameter to evaluated the degree of osteogenesis ,so blood sampling from femurvein was aspirated at 1st ,2nd ,3rd and 4th weeks respectivelly for biochemical analysis.Results :Statistical analysis showed that there is significant elevation of serum (ALP) inexperimental group at day 15 and 21 comparing to control group .Conclusion:Hydroxyapatite with autogenous bone marrow than it is used alone. has great effect onfacilitating of osteogenesis.